Dewey decimal classification and relative index (v.3)/ schedule 600-999 - Melvil Dewey; Joan S Mitchell (ed.); Julianne Beall (ed.); Rebecca Green(ed.); Giles Martin (ed.); Michael Panzer (ed.) (Dublin, Ohio : OCLC Online Computer Library Center, Inc., 2011)
Schedule 600-999
Keywords: Classification, Dewey Decimal